FSKTM course scheduling system / Ong Suh Pun - Ong , Suh Pun (2002)
Timetabling the courses offered at the Faculty of Computer Science and Information Technology in University of Malaya (FSKTM, UM) is a hard problem faced continually in this faculty. The timetabling problem consists in fixing a sequence of meeting between lecturers and students in a prefixed period of time, often to satisfy a set of constraints. Currently, FSKTM is using the manual system to generate timetable. The manual solution of courses timetabling usually requires days of work and sometimes the solution may be unsatisfactory to some respect. Subsequently, this project paper is conducted to develop an automated FSKTM Course Scheduling System (FCSS) under Web-based application. The purpose of FCSS is to reduce the time and effort needs for generating a tim table in FSKTM. FCSS could generate timetable automatically and publish the timetable on the Web. In this system, an efficient scheduling engine will solve conflicting issues in timetabling problem. The engine will generate timetable automatically after checking the crashes between lectures, students, rooms and other hard constraints. All the information needed such as information about rooms, courses and lecturers are stored in the database. The system will interact with the end user through the interface subsystem.Basically, there are three modules in FCSS, which are administration module, course scheduling module and user module. Administrators could access administration module to manage and keep track of the database's information. Timetable coordinator could generate timetable using the scheduling engine in the course scheduling module. In user module, students and lecturers could view and print their timetable through the internet.